Case management effectiveness in reducing hospital use: a systematic review. (11th November 2016) - Joo, J.Y.; Liu, M.F.
Abstract : Aim: This systematic review synthesizes recent evidence of the effectiveness of case management in reducing hospital use by individuals with chronic illnesses. Background: Hospital use by individuals with chronic illnesses accounts for 66% of healthcare costs in the United States. its has been cited as care coordination that can reduce healthcare costs; however, its effectiveness in improving hospital use outcomes is contradictory, and no review has yet synthesized recent studies of case management with respect to hospital use outcomes. Methods: This systematic review followed the Cochrane processes and was guided by use of PRISMA statements. Five electronic databases were searched to obtain randomized controlled trials published within the last 10 years that evaluated case management hospital use as a primary outcome by individuals with chronic illnesses. Results: Ten studies published between 2007 and 2015 were retrieved and assessed for risk of methodological bias. All studies used case management as an intervention, focused on transitional care services and reported hospital use, including readmissions and emergency department and hospital visits, as a primary outcome. Analysis of the studies showed that case management greatly reduced hospital readmissions and emergency department visits. Limitations: Only studies published in English were searched, and retrieved studies tended to report positive results. Conclusions: There was strong evidence of significant reductions in hospital use with case management as an intervention. However, other results about the efffectiveness of case management remain mixed; more rigorously designed studies with case management interventions are needed. Implications for nursing and health policy: The complexity and cost of chronic illnesses means that case management should be considered as a tool to improve quality of care and lower healthcare costs.